Identificaç\~ao das barreiras ao comércio no Mercosul: A percepç\~ao das empresas exportadoras brasileiras - Honorio Kume; Patrícia Anderson; Márcio de Oliveira Júnior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2001)
– The main aim of this paper is to identify and to analyze the presence of Non Tariff Barriers (NTBs) imposed on Brazilian exports to the other three Mercosur's member countries. The NTBs were identified through interviews with selected Brazilian companies from three sectors - Footwear, Frozen Chicken and Steel Products - and through 412 questionaries answered by Brazilian exporting firms. During the interviews, the main NTBs identified for each sector were: a) Footwear: labeling regulations, industrial standards and regulations, licensing and customs clearance procedures; b) Frozen Chicken: sanitary regulations, antidumping files and customs clearance procedures; c) Steel Products: safety and industrial standards and regulations, antidumping duties, discriminatory bilateral agreements and customs clearance procedures. Concerning the questionaries, a list with 16 non tariff barriers to trade divided into visible and non visible barriers were presented to the exporting firms. They were asked to identify which NTBs faced by them when trading with the other Mercosur's member countries and what was their importance. The level of importance ranged from one (little important) to six (very important). According to the companies the NTBs that affect them most in their intra Mercosur trade are: a) Visible barriers: freight and insurance costs and expenses due to customs procedures; b) Non visible barriers: labeling regulations, customs procedures, previous inspection of products and safety and industrial standards and regulations. Once identified the main NTBs that affect Brazilian companies sales to the other three Mercosur's member countries, one can propose actions to eliminate them and increase trade among the countries. Such actions are: a) harmonization of health and sanitary regulations and quality standards and acceptance of certificates issued by government agencies or previously selected certifying companies of any member country; b) prohibition of antidumping duties in intra Mercosur trade. The dumping cases should be investigated and judged by domestic agencies dealing with antitrust and competition policies; c) adoption of uniform customs procedures for intra Mercosur trade by the four member countries.
Keywords: 330; Nichttarifäre Handelshemmnisse; Mercosur-Staaten